Expand and simplify
(x-3) (x-3) +2(x-3) -8=0
(x-3+2)(x-3)-8=0
(x-1)(x-3)-8=0
x^2 -4x +3-8=0
x^2 - 4x -5=0
x^2 -5x +x-5=0
x(x-5)+x-5=0
(x+1)(x-5)=0
x= - 1, 5
11.7
Formula: a^2 + b^2 = c^2
so substitute the numbers like this:
10^2 + 6^2 = c^2
both 10^2 and 6^2 are perfect squares:
10 × 10= 100 and 6 × 6= 36
100 + 36= c^2
add:
100 + 36 =
136 = c^2
now in order to get rid of the squared, you put it into a radical:
√136 = √c^2
note: whatever you do on one side, you do to the other
it's easier to use the calculator for this so put √136 and you're gonna get 11.66
since it's asking you to round it to the nearest tenth:
11.66 = 11.7
sorry if the explanation is kinda long ✋ i tried explaining it better in the end but i failed
Answer:
$16
Step-by-step explanation: I did the math in the comments.
Answer: C: Yes
Step-by-step explanation:
C on edge 2021